Transformation of non-apatite inorganic phosphorus to apatite phosphorus: a novel pathway for sediment phosphorus immobilization via iron-calcium synergistic treatment - Li, Wei; Sheng, Weijing; Liu, Shuqiong; Dai, Taotao; Zhong, Jiayou; Ren, Wenjing; Chen, Yuwei; Zhong, Yan; Luo, Liancong (Frontiers in Environmental Science, 2025)
Iron and calcium salts are two commonly used inactivators of sediment phosphorus (P). However, there is limited research on the effectiveness of their combined use. In this study, two enclosures (each 600 m2) were constructed in a eutrophic sub-lake within Poyang Lake (the largest freshwater lake in China), to examine the inhibitory effect of iron-calcium combined treatment (Fe&Ca treatment) on sediment P release. Subsequently, a sediment incubation experiment was conducted to investigate the impact of Fe treatment alone, Ca treatment alone, and Fe&Ca treatment on sediment P release fluxes and P fractions. The enclosure experiment demonstrated that the Fe&Ca treatment resulted in a decrease of 0.65 times in non-apatite inorganic P (NAIP) content in sediment, and an increase of 2.87 times in apatite P (AP) content. The sediment P release in the treated enclosure was significantly reduced by up to 90% under alkaline conditions compared to the control enclosure. In the sediment incubation experiment, Fe&Ca treatment effectively restrained P release and enhanced sediment AP content while reduced NAIP content. The transformation from NAIP to AP was likely primarily driven by Ca treatment, while Fe&Ca treatment stabilized water pH and consequently inhibited the release of sediment P and nitrogen. This study is the first to validate this transformation pathway and its inhibitory effect on P release. These findings emphasize the effectiveness of iron and calcium combination for minimizing the risk of P release from sediments, thereby offering a promising approach for in situ P control in lakes.